2016
DOI: 10.2131/jts.41.489
|View full text |Cite
|
Sign up to set email alerts
|

Simple analysis of total mercury and methylmercury in seafood using heating vaporization atomic absorption spectrometry

Abstract: This study aimed to develop a simpler method for determining total mercury (T-Hg) and methylmercury (MeHg) in biological samples by using methyl isobutyl ketone (MIBK) in the degreasing step. The fat in the samples was extracted by MIBK to the upper phase. T-Hg transferred into the water phase. This was followed by the extraction of MeHg from the water phase using HBr, CuCl2 and toluene. The MeHg fraction was reverse-extracted into L-cysteine-sodium acetate solution from toluene. The concentrations of T-Hg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Similarly, Hg concentrations in sardines were lower than the Hg levels in canned sardines (117 ng/g, 141 ng/g, and 143 ng/g) reported by Boadi et al (2011). The current study found that the percentage of MeHg in T-Hg in canned fish samples ranged from 90.4% to 100%, which was consistent with levels found in fish, squid and shrimp in previous studies (Bloom, 1992;Yoshimoto et al, 2016;Hoang et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Hg concentrations in sardines were lower than the Hg levels in canned sardines (117 ng/g, 141 ng/g, and 143 ng/g) reported by Boadi et al (2011). The current study found that the percentage of MeHg in T-Hg in canned fish samples ranged from 90.4% to 100%, which was consistent with levels found in fish, squid and shrimp in previous studies (Bloom, 1992;Yoshimoto et al, 2016;Hoang et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Extraction of T-Hg and MeHg from canned fish samples followed the protocol described previously (Miyamoto et al, 2010;Yoshimoto et al, 2016). Briefly, the muscle of canned fish samples was solubilized with 0.1% Cys solution (1 mL) and 5 M NaOH (1 mL), then incubated at 80°C for 1 hr with vortexing every 10 min.…”
Section: Determination Of Total Mercury and Methylmercury In Canned Fishmentioning
confidence: 99%
“…THg and MeHg extractions from earthworms were performed based on the reported protocol for biological tissue (Miyamoto et al, 2010;Yoshimoto et al, 2016). For THg extraction, an aliquot of approximately 0.1 g (dw) of each earthworm sample was weighed in 15 mL polypropylene (PP) tubes with screw caps, in triplicate.…”
Section: Extraction Of Mercury and Methylmercurymentioning
confidence: 99%
“…CRM165 (5.340 ± 0.140 mg kg -1 ) showed a THg recovery of 97.6 ± 4.3% (i.e., 5.210 ± 0.170 mg kg -1 ) with a CV of 4.4%, and CRM250 (i.e., 0.610 ± 0.020 mg kg -1 ) showed a recovery of 98.01 ± 2.9% (i.e., 0.580 ± 0.020 mg kg -1 ) with a CV of 2.95%. Therefore, we used 97.5% (the mean CRM MeHg recovery for swordfish and codfish) as the correction factor for calculating the concentration of MeHg extracted from earthworm samples (Yoshimoto et al, 2016;Miyamoto et al, 2010). The recovery tests for soil THg were measured using CRM lake sediments 7303-a (CRM E-0190) and marine sediments 7302-a (CRM A-0210).…”
Section: Mercury Determination Quality Control (Qc) and Quality Assmentioning
confidence: 99%
“…T‐Hg concentrations in blood and sciatic nerve were measured with a direct thermal decomposition Hg analyzer (SP‐3D and MA‐3000; Nippon Instruments, Tokyo, Japan) as previously described (Yamamoto et al, ; Yamamoto et al, ). T‐Hg and MeHg contents in brain tissue were measured using a protocol we developed previously (Hoang, Do, et al, ; Hoang, Sakamoto, & Yamamoto, ; Miyamoto, Kuwana, Ando, Yamamoto, & Nakano, ; Yoshimoto et al, ). The samples were solubilized with 0.1% Cys solution (1 mL) and 5 m NaOH (1 mL), then incubated at 80°C for 1 hour with vortexing every 10 minutes.…”
Section: Methodsmentioning
confidence: 99%